SYMMETRY AS CONCEPTUAL METAPHOR IN WALKER'S THE COLOR PURPLE - Tapia, Elena (International Journal of English Studies, 2003)
The author analyzes three types of the conceptual metaphor of embodied symmetry in AliceWalker's novel, The color purple (1982). These metaphorical projections, perceived asequilibrium and its breakage in abstract phenomena, enable readers to reexamine issues of race,non-traditional families, and gender roles. The dis/equilibrium emerges in the novel's epistolarystructure. Biological equilibrium breaks in incidents of rape and incest. Walker creates charactersin the novel through default-concept opposites of black/white, submissive/dominant, male/femaleand others. These contraries foreground issues of race and gender. The novel's asymmetriesengage readers, leading them to rethink individual character histories and motives. The removalof objects (e.g., rape, mothers deprived of children) suggests conceptual asymmetry and alertsreaders to parallel themes of sexual and racial oppression. Subjugation sometimes subtle,sometimes blatant- manifests in simple oppositions. In epistemological terms, readers seekcausal explanations for the asymmetries of the narrative, interpreting each to recover its history.